High throughput newborn screening for aromatic ʟ-amino-acid decarboxylase deficiency by analysis of concentrations of 3-O-methyldopa from dried blood spots - Brennenstuhl, Heiko; Kohlmüller, Dirk; Gramer, Gwendolyn; Garbade, Sven; Syrbe, Steffen; Feyh, Patrik; Kölker, Stefan; Okun, Jürgen G.; Hoffmann, Georg F.; Opladen, Thomas (Journal of inherited metabolic disease, 2020)
Aromatic l-amino-acid decarboxylase (AADC) deficiency is an inherited disorder of biogenic amine metabolism with a broad neurological phenotype. The clinical symptoms overlap with other diseases resulting in an often delayed diagnosis. Innovative disease-changing treatment options, particularly gene therapy, have emphasised the need for an early diagnosis. We describe the first method for 3-O-methyldopa (3-OMD) analysis in dried blood spots (DBS) suitable for high throughput newborn screening (NBS). We established a novel tandem mass spectrometry method to quantify 3-OMD in DBS and successfully tested it in 38 888 unaffected newborns, 14 heterozygous DDC variant carriers, seven known AADC deficient patients, and 1079 healthy control subjects. 3-OMD concentrations in 38 888 healthy newborns revealed a mean of 1.16 μmol/L (SD = 0.31, range 0.31-4.6 μmol/L). 1079 non-AADC control subjects (0-18 years) showed a mean 3-OMD concentration of 0.78 μmol/L (SD = 1.75, range 0.24-2.36 μmol/L) with a negative correlation with age. Inter- and intra-assay variability was low, and 3-OMD was stable over 32 days under different storage conditions. We identified seven confirmed AADC deficient patients (mean 3-OMD 9.88 μmol/L [SD = 13.42, range 1.82-36.93 μmol/L]). The highest concentration of 3-OMD was found in a NBS filter card of a confirmed AADC deficient patient with a mean 3-OMD of 35.95 μmol/L. 14 DDC variant carriers showed normal 3-OMD concentrations. We demonstrate a novel high-throughput method to measure 3-OMD in DBS, which allows integration in existing NBS programs enabling early diagnosis of AADC deficiency.
First published: 18 December 2019
Gesehen am 04.06.2020